Một số khó khăn và đề xuất giải pháp trong đánh giá trực tuyến khi giảng dạy môn Tiếng Anh tại Trường Đại học Cảnh sát Nhân dân - Lê, Hương Hoa; Nguyễn, Mậu Vũ (Tạp chí Giáo dục, 2025)
The digitalization process in higher education is reshaping teaching and assessment methods, particularly in subjects that require high interaction, such as foreign languages. In this context, implementing online assessment poses many challenges for lecturers, especially at training institutions with special requirements such as the People's Police University. This article aims to identify the outstanding difficulties in the online assessment process and propose appropriate improvement directions. The study employed a qualitative method, conducting in-depth semi-structured interviews with 15 English lecturers at the People's Police University. The results showed five main groups of challenges: (1) Limitations in operating the assessment platform; (2) Difficulty in ensuring authenticity and preventing cheating; (3) Pressure on grading and limited resources; (4) Difficulty in assessing nonverbal skills and group interaction; (5) Lack of theoretical application orientation in assessment design. On this basis, the study proposes several solutions: organizing training on assessment technology capacity, designing authentic assessment tools, applying real-time assessment, and developing comprehensive assessment forms, such as e-portfolios, group presentations, and peer feedback. The application of the TPACK model, combined with the digital version of Bloom's Taxonomy and the SAMR model, is emphasized as a crucial theoretical basis to help lecturers enhance the quality of digital assessment in English.